Mapping and rebranding ornamental fish farming in Depok, West Java, contributions to the SDGs - Harriz, Muhammad Alfathan; Setiyowati, Harlis; Akbariani, Nurhaliza Vania (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: This study aims to identify and prioritize effective rebranding strategies for the ornamental fish farming industry in Depok, West Java, using the Analytic Hierarchy Process (AHP) to address challenges such as limited market access, environmental sustainability issues, and economic feasibility concerns while aligning with Sustainable Development Goals (SDGs). Research Methodology: The research employs a mixed-method approach, combining qualitative research through in-depth interviews with key stakeholders and quantitative analysis using the AHP to systematically evaluate and prioritize rebranding strategies based on multiple criteria. Results: The study identified market access as the most critical criterion, followed by environmental sustainability and economic feasibility, with digital marketing emerging as the most effective rebranding strategy, scoring 0.67, followed by sustainability certification (0.22) and community outreach programs (0.11). Limitations: The research is limited by a small sample size, potentially affecting result generalizability. The AHP methodology introduces possible subjective biases through pairwise comparisons. The study's regional specificity may constrain broader applicability. Furthermore, the emphasis on rebranding strategies may not encompass all potential solutions to industry challenges. Contribution: This research provides actionable insights for stakeholders in the ornamental fish farming industry to implement sustainable development strategies, aligning with SDGs 1, 8, and 14. It offers a systematic approach to decision-making through the application of AHP. Novelty: This study innovatively applies the AHP to rebranding strategies in ornamental fish farming, uniquely integrating sustainable development principles with quantitative decision-making. This approach offers a new paradigm for strategic planning in aquaculture, contrasting with traditional qualitative methods in the field.